33 Tolerability of neuroleptics for tourette syndrome. Issue 8 (13th July 2017) - Stern, Jeremy; Rana, Raafae; Simmons, Helen
Abstract : Objective: Pharmacological treatments of Tourette Syndrome (TS) are variable in their efficacy and tolerability between patients. Most studies examine a single drug with a focus on effective treatment. We aimed to identify the frequency of treatment limiting adverse effects seen in TS patients prescribed one of the most commonly used first line groups of drugs, neuroleptics. Method: 185 sets of clinical notes from a dedicated Tic Disorder clinic were retrospectively reviewed. These represented patients with surnames starting A-G over a 10 year period and 107 were over 18 years old. Neuroleptic prescriptions and the outcome in terms of tolerability at the next clinical review was recorded, but mentions of historical treatment before reaching our clinic were not included. Results: 111/185 members of the cohort were not prescribed neuroleptics, or were not at the time of study monitored for at least one review visit. The most used drug was Aripiprazole in 66 patients – 75% of all neuroleptic drugs prescribed. 18% were stopped due to side effects and 12% were reduced in dose due to side effects; so, 30% of Aripiprazole prescriptions were associated with limiting adverse side effects. Tiredness was most common (n=8), followed by weight gain (n=5) and sedation (n=4). 15 prescriptions of Aripiprazole were associated with no reported side effects. 22 patients were prescribed other neuroleptics and further information will be presented. Conclusion: The majority of patients do not report adverse effects and continue with their Aripiprazole prescription. Around 18% discontinued the drug due to adverse effects, in line with previous data. The study was limited by short follow-up times as other patients may subsequently experience treatment-limiting side effects after successful early review. In recent years Aripiprazole tended to be the first line neuroleptic used, so data on other less used alternatives may be biassed by being prescribed after one agent had already failed due to adverse effects or lack of efficacy.